Cost-effectiveness analysis of adebrelimab combined with chemotherapy for extensive-stage small cell lung cancer - You, Maojin; Chen, Ruijia; Wu, Qingfeng; Zhu, Wei; He, Ying; Huang, Yufan (Frontiers in Pharmacology, 2022)
Background: The findings of the CAPSTONE-1 trial showed that adebrelimab in combination with chemotherapy (etoposide-carboplatin) (ADCHM) is clinically beneficial as a first-line treatment for patients with extensive-stage small cell lung cancer (ES-SCLC), compared with placebo plus chemotherapy (PLCHM, etoposide-carboplatin). However, owing to the higher cost of adebrelimab, it is unclear whether ADCHM is cost-effective compared with PLCHM. This study aimed to evaluate the cost-effectiveness of ADCHM as a first-line treatment for patients with ES-SCLC from the perspective of the Chinese healthcare system. Methods: A Markov model with three health states was developed to assess the cost-effectiveness of ADCHM as a first-line treatment option with ES-SCLC. Clinical data were obtained from the CAPSTONE-1 trial. Costs of the drug were calculated at national tender prices, and other costs and utility values were obtained from published literature. The outcomes included life years (LYs), quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICERs). One-way sensitivity analysis and probabilistic sensitivity analysis were used to validate the robustness of the model. Results: The ADCHM group achieved 1.21 QALYs (2.47 LYs) for $25,312, whereas the PLCHM group achieved 0.81 QALYs (1.59 LYs) for $14,846. The ICER for ADCHM versus PLCHM was $25914 per QALY gained. The variables with the greatest impact on the model results were the utility value of progressive disease, the utility value of progression-free survival, and the price of adebrelimab (100 mg). At a willingness-to-pay threshold of $37,653/QALY, ADCHM had an 89.1% probability of being cost-effective compared with PLCHM. Conclusions: ADCHM may be a cost-effective first-line treatment strategy for ES-SCLC from the perspective of the Chinese healthcare system.